Imperial Rhetoric and Revolutionary Practice: The Greek 1821 - Dialla, Ada A. (Historein, 2022)
The article focuses on the revolutionary period of 1821 and examines how the bloody uprising of the Greeks against the Ottomans, in conjunction with the international environment, transformed the notion of the nation. Before the revolution, the term “nation” had mostly cultural connotations and, from a political point of view, was a neutral category within an imperial framework, without claims to be the primary and the dominant element of political identity. The revolutionary period transformed the perception of the nation into an active political and social force and into the most important actor/subject of the historical and political processes.